Corrigendum to “Impact of physical and biological processes on temporal variations of the ocean carbon sink in the mid-latitude North Atlantic (2002–2016)” (Progress in Oceanography (2020) 180, (S0079661119304033), (10.1016/j.pocean.2019.102223)) - Macovei, VA; Hartman, SE; Schuster, U; Torres-Valdés, S; Moore, CM; Sanders, RJ (Progress in Oceanography, 2020)
This is the final version. Available from Elsevier via the DOI in this record The article to which this is the corrigendum is available in ORE at http://hdl.handle.net/10871/120375 The authors regret that we omitted acknowledgement of the ‘iFADO EAPA_165/2016 that covered work at the PAP-SO’. The authors would like to apologise for any inconvenience caused.